A formação de educadores especializados em âmbito penitenciário, na perspectiva da pedagogia social - Emilio Lucio-Villegas Ramos (Universidade do Minho, 2006)
In this article the author try to develop one trainings proposal for educators from Social Educations perspective. We emphasize our attention about educators work in prison. We make a pathway to rehabilitate measures that we confront to punitive measures. We stress a community view of prison issue. In our opinion, community focus suppose educational focus. After this matters, we develop a proposal to initial´ and continuing´ training for educators work in this field.